2011
DOI: 10.1039/c0sm01275k
|View full text |Cite
|
Sign up to set email alerts
|

Controlled self-assembly of α-helix-decorated peptide nanostructures

Abstract: This study describes a strategy to control the degree of a-helix stabilization and the shape of a-helix-decorated nanostructures. Coassembly of a macrocyclic peptide and a b-sheet peptide diminished steric clashes between helical peptide segments, further stabilizing a-helices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…It is well known that α ‐helical structures play an important role in determining protein structures and functions []. Peptides with α ‐helical secondary structure are important building blocks in the field of molecular self‐assembly []. Some nanostructures are made by using peptides with α ‐helical conformation.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that α ‐helical structures play an important role in determining protein structures and functions []. Peptides with α ‐helical secondary structure are important building blocks in the field of molecular self‐assembly []. Some nanostructures are made by using peptides with α ‐helical conformation.…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56][57][58][59] To this aim, different stimuli have been used like polarity of the medium, pH, enzymatic reactions, dilution or the presence of chemicals and reducing agents. [60][61][62][63][64][65][66][67][68][69] Here we report on the design, synthesis and characterization of different Gemini Amphiphilic Pseudopeptides (thereafter named GAPs) 70 able to self-assemble into nanostructures displaying different shapes like fibers, tubes, tapes or vesicles. More interestingly, the self-assembling process can be controlled through the polarity of the environment and, for some specific examples, can be switched between fibers and vesicles by simple variation of the pH.…”
Section: Introductionmentioning
confidence: 99%
“…The gradual decrease in the intensity of negative bands at t = 12 hours was observed for all the peptides suggesting the molecular aggregation due to intermolecular interactions. It has been reported that intermolecular interactions involved in peptides are important for self‐assembling and peptide nanostructures …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that intermolecular interactions involved in peptides are important for self-assembling and peptide nanostructures. [40][41][42] The self-assembled structures formed by the hybrid peptides P1…”
Section: Self-assembling Studiesmentioning
confidence: 99%